The Effect of Social Media Technology, Packaging and Online Promotion on Increasing Sales of Food Products Group of Mothers in Bojong Kulur Village, Bogor - Elfa Setiawan; Endah Fantini; Samsudin Samsudin (Majalah Ilmiah Bijak, 2021)
This study had a goal to detemine the effect of media social technology, packaging, and online promotionÂ  on increasing sales of culinary products group of women in Bojong Kulur village, Bogor, West Java. It also aimed to analyze the most dominant factor in increasing the sales. There were 175 respondents who were taken randomly in Bojong Kulur village area during the period of January to May 2021. The technique of Incidental Sampling was used to gather questionnaires from producers and consumers. Descriptive statistical analysis using SPSS version of 22 was used as the method of data analysis in this study.Research result showed that variable of Media Social Technology, Packaging, and Online Promotion, and Packaging influenced the variable Sales Increase. Based on the result, it was found that the calculated F value was 66.567 > F table 3.05 and the sig value. of 0.000 < 0.05. It also concluded that concluded that those three independant variables have a simultaneous effect on increasing sales as the dependant variable.